The Influence Of Perceived Ease Of Use, Perceived Usefulness, And Promotion On Shopeepay E-Wallet On Consumptive Behavior Of Pontianak City Students - Ramadan, Muhammad; M, Neni Triana (UNIVERSITAS PAKUAN, 2024)
The shift in lifestyle has transformed payment systems in West Kalimantan, moving toward cashless transactions. Non-cash payments, particularly through e-wallets, have become increasingly popular compared to traditional cash payments. This change in consumer behavior stems from various factors. This study analyzes data on server-based electronic transactions in West Kalimantan from 2021 to 2024. However, uncontrolled use of e-wallets during shopping can lead to excessive purchases of non-priority items, often unnoticed by users, resulting in consumptive behavior. This research examines the impact of Perceived Ease of Use, Perceived Usefulness, and Promotion on the consumptive behavior of ShopeePay users among university students in Pontianak City. A quantitative associative research design was employed to explore relationships between variables. Data were gathered using structured questionnaires distributed to active students in Pontianak, measured with a Likert scale, and analyzed using Structural Equation Modeling (SEM) via SmartPLS 3.0 software. The findings demonstrate that Perceived Ease of Use, Perceived Usefulness, and Promotion significantly influence consumptive behavior. Ease of use minimizes transaction barriers and promotes spending, perceived usefulness enhances efficiency and encourages frequent use, while promotions, such as discounts and cashback, have the strongest effect by triggering impulse purchases. Although FinTech innovations like ShopeePay offer convenience, they also pose challenges in managing spending habits. The study underscores the need for financial literacy programs and awareness campaigns to encourage responsible financial behavior. Future research should explore broader populations, cultural influences, and group behaviors to provide deeper insights into consumptive patterns. Additionally, e-wallet providers are advised to implement budget control features and financial reminders to assist users in managing transactions more wisely.